2019
DOI: 10.3390/ma12050779
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterial Applications in Photothermal Therapy for Cancer

Abstract: As a result of their unique compositions and properties, nanomaterials have recently seen a tremendous increase in use for novel cancer therapies. By taking advantage of the optical absorption of near-infrared light, researchers have utilized nanostructures such as carbon nanotubes, gold nanorods, and graphene oxide sheets to enhance photothermal therapies and target the effect on the tumor tissue. However, new uses for nanomaterials in targeted cancer therapy are coming to light, and the efficacy of photother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
227
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(229 citation statements)
references
References 73 publications
(85 reference statements)
1
227
0
1
Order By: Relevance
“…34 In particular, novel materials with high optical absorbance in the NIR region for PTT include gold nanoshells, 34 gold nanorods 35,36 and CNTs. [37][38][39] In Table 1, the photothermal therapies utilising different materials and an 808 nm diode laser are demonstrated with the effective laser intensity of 0.7-9.2 W cm À2 . This paper reviews the recent developments of metabolic imaging systems for photochemotherapy using 2D carbon materials of graphene and graphene-based conjugates for cancer disease healing purposes.…”
Section: Introductionmentioning
confidence: 99%
“…34 In particular, novel materials with high optical absorbance in the NIR region for PTT include gold nanoshells, 34 gold nanorods 35,36 and CNTs. [37][38][39] In Table 1, the photothermal therapies utilising different materials and an 808 nm diode laser are demonstrated with the effective laser intensity of 0.7-9.2 W cm À2 . This paper reviews the recent developments of metabolic imaging systems for photochemotherapy using 2D carbon materials of graphene and graphene-based conjugates for cancer disease healing purposes.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, photothermal therapy (PTT) has been demonstrated as a highly effective cancer treatment by many scientists. [7][8][9] Photothermal reagents are designed to accumulate at tumor sites, and when the tumor sites are irradiated with near-infrared (NIR) lasers, site-specific hyperthermia is induced and the cancer cells die. 10,11 The laser is an important element in PTT, and its properties in biological tissues directly affect the therapeutic effect of PTT.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, biological applications of GO and graphene sheets (GS) have been widely investigated, largely due to their potential for mediating photothermal therapy, antibacterial and antimicrobial effects, and as vehicles for drug delivery. [84] GS and GO are recognized as promising candidates for drug and gene delivery, due to several advantageous properties, including large surface area, ability to be non-covalently loaded with drug molecules containing aromatic rings, their intrinsic optical properties, and their relatively low cost. [85] Graphene can interact with both RNA and DNA strands so that they are promising for gene delivery.…”
Section: Biological Propertiesmentioning
confidence: 99%
“…GO exhibits preferential interaction with single-stranded DNA compared to double-stranded DNA and is able to protect the nucleic acids from enzymatic attack by various nucleases. [86] There is an observation in [84] that demonstrates molecular beacon; hairpin shape DNA, non-covalently absorbed on the functionalized nanoscaled graphene oxide. It is then concluded that functionlized nanoscaled graphene oxide has the ability to protect oligonucleotides from enzymatic attack.…”
Section: Biological Propertiesmentioning
confidence: 99%